Preparation and High-Frequency Dielectric Properties of Polytetrafluoroethylene Reinforced Bismaleimide-Triazine ResinGlass Fiber Composites - Delgado, Suchat; Bravo, Nacarid; Raita, Jorge (Journal of Green Energy and Environmental Engineering, 2026)
Addressing the stringent requirements of 5G/6G high-frequency and high-speed communication technologies for printed circuit board (PCB) substrates, this study designed and prepared a polytetrafluoroethylene (PTFE)-filled modified bismaleimide-triazine (BT) resin/glass fiber (GF) composite. The glass fiber cloth was surface-modified with silane coupling agent KH570 to enhance interfacial bonding, and low-dielectric PTFE filler was introduced into the pores of the glass fiber cloth via a high-temperature and high-pressure lamination process; the influence mechanism of PTFE content on the comprehensive properties of the composite was systematically investigated. Results indicate that when the PTFE mass fraction is 5%, the composite achieves optimal comprehensive performance: the dielectric constant (Dk) and dielectric loss (Df) are 4.3 and 0.006 at 1 MHz, and 3.4 and 0.003 at 10 GHz, respectively; the glass transition temperature (Tg) increases to 250℃ (approximately 25℃ higher than that of the pure BT system), the char yield at 800℃ reaches 76.63% (an increase of about 17.55%), the flexural strength remains at 574.7 MPa, and the water contact angle increases to 86.5°. Mechanism analysis reveals that the introduction of PTFE significantly improves the high-frequency dielectric properties of the composite by reducing the polarization degree, filling pores to decrease interfacial polarization losses, and restricting the orientation movement of polar groups. Simultaneously, the high bond energy of C-F bonds endows the composite with enhanced thermal stability. However, the high coefficient of thermal expansion (CTE) of PTFE raises the CTE of the composite to approximately 45×10−6∘C−1, which requires further optimization. This material system achieves a significant improvement in dielectric properties while maintaining the high heat resistance and good processability of BT resin, providing a cost-competitive substrate solution for mid-to-high frequency applications such as 5G millimeter-wave antennas and radio frequency front ends.